Kuliner Khas Banjar (Konsep, Filosofi, Identitas Dan Nilai-Nilai Pendidikan Islam) - Khairunnida .; Ali Muammar ZA (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Banjar traditional cuisine is not merely a means of physical fulfillment but also a symbolic medium containing historical, cultural, and Islamic values. This research aims to comprehensively examine Banjar culinary specialties through the lenses of concept, philosophy, identity, and Islamic educational values. Using a descriptive analysis method, this study explores how cooking and consumption practices function as non-formal Islamic education instruments for the community. The results indicate that the concept of Banjar cuisine is inseparable from the principle of halalan thayyiban, where eating activities are integrated with worship and the internalisation of values such as gratitude (syukur), simplicity (zuhud), and social solidarity (ukhuwwah). Identity is reflected through the use of local ingredients and ritual functions in religious ceremonies. Furthermore, culinary traditions serve as a "living curriculum" that instills characters of cleanliness, honesty, and persistence across generations. This study concludes that preserving Banjar cuisine is essential for strengthening Islamic character and cultural identity amidst the challenges of modernization.